Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
E = 1x2x3 + 2x3x4 + 3x4x5 + ... + 9x10x11
E x 4 = 1x2x3x4 + 2x3x4x4 + 3x4x5x4 + ... + 9x10x11x4
E x 4 = 1x2x3x4 + 2x3x4x(5-1) + 3x4x5x(6-2) + ... + 9x10x11x(12-8)
E x 4 = 1x2x3x4 + 2x3x4x5 - 1x2x3x4 + 3x4x5x6 - 2x3x4x5 + ... + 9x10x11x12 - 8x9x10x11.
E x 4 = 9x10x11x12
E = 9x10x11x12 : 4
E = 2970
a)\(3\frac{4}{10}>2\frac{9}{10}\)
b)\(3\frac{4}{10}< 3\frac{9}{10}\)
c)\(5\frac{1}{10}>2\frac{9}{10}\)
d)\(3\frac{4}{10}=3\frac{2}{5}\)
Hok tốt!~
a). 3 9/10 > 2 9/10
b).3 4/10 < 3 9/10
c).5 1/10 > 2 9/10
d).3 4/10 = 3 2/5
a)\(\frac{4}{3.7}+\frac{4}{7.11}+...+\frac{4}{23.27}=\frac{1}{3}-\frac{1}{7}+\frac{1}{7}-\frac{1}{11}+...+\frac{1}{23}-\frac{1}{27}=\frac{1}{3}-\frac{1}{27}=\frac{8}{27}\)
b)\(\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{6.7}=\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{6}-\frac{1}{7}=\frac{1}{2}-\frac{1}{7}=\frac{5}{14}\)
c)\(\frac{2}{3.5}+\frac{2}{5.7}+...+\frac{2}{11.13}+\frac{2}{1.2}+\frac{2}{2.3}+...+\frac{2}{9.10}=\left(\frac{1}{3}-\frac{1}{5}+\frac{1}{5}-\frac{1}{7}+...+\frac{1}{11}-\frac{1}{13}\right)+2\left(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+...+\frac{1}{9}-\frac{1}{10}\right)\)
\(=\frac{1}{3}-\frac{1}{13}+2\left(1-\frac{1}{10}\right)=\frac{10}{39}+\frac{9}{5}=\frac{401}{195}\)
A=1/1*2+1/2*3+...+1/9*10
=1-1/2+1/2-1/3+...+1/9-1/10
=(1-1/10)+(1/2-1/2)+...+(1/9-1/9)
=(10/10-1/10)+0+...+0=9/10
\(B=\frac{1}{1.2.3.4}+\frac{1}{2.3.4.5}+\frac{1}{3.4.5.6}+...+\frac{1}{8.9.10.11}+\frac{1}{9.10.11.12}\)
\(B=\frac{1}{3}\left(\frac{3}{1.2.3.4}+\frac{3}{2.3.4.5}+\frac{3}{3.4.5.6}+...+\frac{3}{8.9.10.11}+\frac{3}{9.10.11.12}\right)\)
\(B=\frac{1}{3}\left(\frac{1}{1.2.3}-\frac{1}{2.3.4}+\frac{1}{2.3.4}-\frac{1}{3.4.5}+...+\frac{1}{9.10.11}-\frac{1}{10.11.12}\right)\)
\(B=\frac{1}{3}\left(\frac{1}{1.2.3}-\frac{1}{10.11.12}\right)\)
\(B=\frac{1}{3}.\frac{73}{440}=\frac{43}{1320}\)
A=1*2*3+3*4+4*5*6*7+7*8+8*9*10